Proteasome subunit beta type 1 interacts directly with Rheb and regulates the cell cycle in Cashmere goat fetal fibroblasts. Issue 5 (3rd September 2017) - Wang, Yanfeng; Guo, Zhixin; Liu, Mingtao; Zhao, Keyu; Feng, Xue; Zheng, Xu; Wang, Xiaojing; Hao, Huifang; Guo, Xudong; Wang, Zhigang
ABSTRACT: PSMB1 (proteasome subunit beta type 1) is a core component of the 20S proteasome, and based on its structure, it might have a crucial function in the transcription of certain genes. Rheb (Ras homolog enriched in brain) is a Ras-like small GTPase that acts as an upstream positive regulator of the mechanistic target of rapamycin complex 1 (mTORC1) pathway. We cloned and characterized PSMB1 (KY310590.1) to determine its function in cell cycle progression and proliferation of goat fetal fibroblasts (GFbs). Further, by yeast two-hybrid screen and coimmunoprecipitation, we conformed that PSMB1 interacts directly with Rheb. An siRNA was designed and expressed targeting PSMB1 mRNA in GFbs and inducing cell cycle arrest. Rheb overexpression in GFbs significantly increased the number of S phase cells and growth efficiency compared with control cells. These data indicate that PSMB1 and Rheb have important functions in the cell cycle and proliferation of GFbs, indicating that their interaction governs many processes in GFbs. Abbreviations: GFbs: Cashmere goat fetal fibroblasts; mTOR: The mechanistic target of rapamycin; PSMB1: proteasome subunit beta type 1; Rheb: Ras homolog enriched in brain